Perancangan dan Pengembangan Prototipe Aplikasi Mobile Untuk Lembaga Penghafal Quran Berbasis Android Menggunakan Metode Rapid Application Development - Hakim, Abdul Barir; Ramdhani, Vera (LPPM of STIMIK ESQ, 2017)
This research is motivated by the lack of Quran memorization caused by several factors, including the limited educational facilities and teachers to help memorize the Quran. The recording method of Quran in the House of Quran Daarut Tarbiyah is still using conventional recording that causes the data santri and rote data is not centralized and well documented. For that, through this research has been done design and development of mobile application prototype for the institution of Android-based Quran memorizers. The application development method used is Rapid Application Development (RAD), which corresponds to a short development time and as needed. RAD method consists of four stages namely the stage of planning needs, design, construction and implementation. This research produces a prototype of mobile application for an Android-based Quran memorizing institution that is aimed at making the Quran House Tarbiyah LIPIA Pasar Minggu can be simplified in daily recitation or evaluation of institutions, teachers, and students.